Serum alpha-1 antitrypsin in acute ischemic stroke: A prospective pilot study. (June 2020) - Mahta, Ali; Yaghi, Shadi; Reznik, Michael E.; Thompson, Bradford B.; Wendell, Linda C.; Rao, Shyam; Potter, Nicholas S.; Dakay, Katarina B.; Cutting, Shawna; Mac Grory, Brian; Burton, Tina; Saad, Ali; et al.
Highlights: Alpha-1 antitrypsin (AAT) may play a protective role against atherosclerosis. Low serum level of AAT maybe associated with atherosclerosis on major arteries. Serum AAT maybe used as a biomarker to differentiate stroke mechanism. Abstract: Background: Alpha-1 antitrypsin (AAT) is a potent anti-protease enzyme which may play a role in arterial wall stability. A variant of its encoding gene has been recently linked to ischemic stroke due to large artery atherosclerosis (LAA). We sought to explore potential relationships between ischemic stroke mechanisms, atherosclerosis burden and serum AAT levels. Methods: We performed a prospective observational study of consecutive patients with acute ischemic stroke who were admitted to an academic comprehensive stroke center over a three-month period. Blood samples were collected within 24 h of hospital admission, and stroke subtype classification was determined based on modified TOAST criteria. Modified Woodcock scoring system was used to quantify calcification of major cervico-cranial arteries as a surrogate for atherosclerosis burden. Linear regression analysis was used to assess the association between serum AAT levels and calcification scores, both as continuous variables. Results: Among eighteen patients met our inclusion criteria and were enrolled in our study, 10 patients (56%) were men; mean age was 66 (SD 12.5); median NIH stroke scale was 4 (IQR 9.5); 8 patients (44%) had stroke due to LAA. The median serum level of AAT was 140 mg/dl (IQR 41.7) for patients with LAA-related stroke, and 148.5 mg/dl (IQR 37.7) for patients with other stroke mechanisms (p = 0.26). Higher serum AAT levels was associated with lower modified Woodcock calcification scores. (p-value = 0.038) Conclusions: Measurement of AAT levels in patients with acute stroke is feasible, and there may be associations between AAT levels and stroke mechanism that warrant further study in larger samples.